The (im)permanence of fading smoke : a conservation case study of Diane Victor’s soot drawings - McGinn, Isabelle (University of Pretoria, 2022)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))-- University of Pretoria, 2021.